Conducting Linguistic Experiments Online With OpenSesame and OSWeb. Issue 4 (20th June 2022) - Mathôt, Sebastiaan; March, Jennifer
Abstract: In this Methods Showcase Article, we outline a workflow for running behavioral experiments online, with a focus on experiments that rely on presentation of complex stimuli and measurement of reaction times, which includes many psycholinguistic experiments. The workflow that we describe here relies on three tools: OpenSesame/OSWeb (open source) provides a user‐friendly graphical interface for developing experiments; JATOS (open source) is server software for hosting experiments; and Prolific (commercial) is a platform for recruiting participants. These three tools integrate well with each other and together provide a workflow that requires little technical expertise. We discuss, and illustrate through an example study, several challenges that are associated with running online experiments, including temporal precision, the implementation of counterbalancing, data quality, and issues related to privacy and ethics. We conclude that these challenges are real but surmountable, and that in many cases online experiments are a viable alternative to laboratory‐based experiments. Abstract :